2012
DOI: 10.1111/j.1751-7176.2012.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Pill Combination of Telmisartan/Amlodipine in Patients With Severe Hypertension: Results From the TEAMSTA Severe HTN Study

Abstract: 6This 8-week, randomized, double-blind, controlled study compared efficacy and tolerability of telmisartan ⁄ amlodipine (T ⁄ A) single-pill combination (SPC) vs the respective monotherapies in 858 patients with severe hypertension (systolic ⁄ diastolic blood pressure [SBP ⁄ DBP] !180 ⁄ 95 mm Hg). At 8 weeks, T ⁄ A provided significantly greater reductions from baseline in seated trough cuff SBP ⁄ DBP ()47.5 mm Hg ⁄ )18.7 mm Hg) vs T (P<.0001) or A (P=.0002) monotherapy; superior reductions were also evident at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
15

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 43 publications
1
21
0
15
Order By: Relevance
“…Trials showed that the addition of amlodipine to an ARB resulted in greater BP reductions compared to each component at similar doses. More patients in the combination therapy groups responded to achieve the target BP compared with component monotherapies and with comparable adverse events (7275). Trials performed in South Korea and Japan have also shown beneficial effects of adding amlodipine to losartan and candesartan but these combinations of losartan/amlodipine and candesartan/amlodipine are not approved in the U.S. (7677).…”
Section: Efficacy Of Arbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials showed that the addition of amlodipine to an ARB resulted in greater BP reductions compared to each component at similar doses. More patients in the combination therapy groups responded to achieve the target BP compared with component monotherapies and with comparable adverse events (7275). Trials performed in South Korea and Japan have also shown beneficial effects of adding amlodipine to losartan and candesartan but these combinations of losartan/amlodipine and candesartan/amlodipine are not approved in the U.S. (7677).…”
Section: Efficacy Of Arbsmentioning
confidence: 99%
“…Reported serious adverse events were low in number (0.7% vs 0.9% and 0.9%, respectively). The frequency of peripheral edema was more common with amlodipine monotherapy compared with combination therapy (13.2 versus 9.3%, respectively) (75). …”
Section: Safety and Tolerability Of Arbs In Hypertensionmentioning
confidence: 99%
“…In international studies, the T/A combination compared with the respective monotherapies has also been shown to provide superior 24-hour BP lowering in patients with mild-to-moderate hypertension [42] and significantly greater BP reductions and higher BP goal and response rates in patients with severe hypertension [43]. Planned and post hoc pooled analysis of data from clinical trials have shown the T/A SPC to be efficacious and well tolerated in hypertensive patients with added risk factors, including obesity, diabetes, metabolic syndrome, renal impairment, and elevated SBP [4446].…”
Section: Discussionmentioning
confidence: 99%
“…при тяжелой, неконтролируемой АГ, со-путствующем СД 2 типа, ожирении, МС. Применение комбинации телмисартана и амлодипина позволяет до-биться снижения уровня АД и поддержания его целе-вых значений у больных высокого риска, включая па-циентов с тяжелой АГ, СД 2 типа и ожирением [24].…”
Section: диагностика избыточной массы тела и ожиренияunclassified